Contribution Of The Sociology Of Religion In The Perspective Of Dogmatic Theology - Benny Agustinus Triangga Prayitno; Tomi Yulianto (LPPM Universitas PGRI Sumatera Barat, 2024)
In this article the author offers an idea about contribution of the sociology of religion to theology. Traditional approach of doing theology often considers culture and all its elements just as an object of theological enterprise. The biblical text is the only valid and authentical source of theological reflection. As a result, people tends to underestimate the value containing in people religious expressions and experiences. The author does not accept such a view. He is of the opinion that people religious expressions and experiences must be regarded as one of authentic source of doing theology. Equal attention and honor must be given to both: biblical text and cultural text if we want to find a meaningful expression and experience of God’s love and salvation work in our daily activity. From this perspective the author throws a new light to reconsider the task of theological reflection. It is not just to repeat or to receive meaning which has alredy been formulated both in the bible and in the history of theological discussion. Theology must be understood more as an attempt to create or to make a meaning which help people in every given time. Theology is for the author has to be considered more as a meaning making exercise, not just as a meaning receving work.